Atlanta, Ga Paper - Discussion of Mr. Chase's paper on Southern Magnetites (see p. 551) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1896)
E. C. Pechin, Buchanan, Va.: I am sorry to see the table appended to Mr. Chase's excellent paper. In the discussion at the same meeting, on "Notes on a Southern Coal-Washing Plant," Prof. Phillips very properly says: " There is no use in giving an analysis as representing a coal when it does not do so. It gives a wrong impression of the conditions under which business is conducted." The same may be said about ores. I have no personal knowledge of the ores in many of the localities given in Mr. Chase's table; but if these are to be judged by what is positively known of the Cranberry ores, the analyses are grossly misleading. The furnace-shipments from Cranberry have rarely reached 44 per cent. of iron, and any such percentage as 58 or 66 or 68 can only have come from hand-picked specimens. Indeed, with any such percentages, Mr. Chase's paper would have been superfluous, because concentration would be unnecessary. Besides, the paper itself (page 553) gives the fact that the Cranberry average is 42 to 43 per cent. Why should a table be appended, contradicting this statement of the text ? Let us always have the exact conditions under which business may be conducted. "Boom" and business analyses are widely different.